High-bandwidth millimetre wave multiple-input multiple-output antenna for 38 GHz 5G mobile applications - Md. Ashraful Haque; Md. Kawsar Ahmed; Narinderjit Singh Sawaran Singh; Md. Afzalur Rahman; Md. Sharif Ahammed; Redwan A. Ananta; Kamal Hossain Nahin; Jamal Hossain Nirob; Liton Chandra Paul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This study assesses the efficacy of an industrial and innovation antenna by scrutinizing its performance using simulations and an equivalent resistor, inductor, and capacitor (RLC) circuit model. By utilizing computer simulation technology (CST) modeling techniques, the antenna’s small dimensions of 37.75×31.75 mm2 are considered concerning the minimum frequency. The antenna functions at a frequency of 38 GHz, with a bandwidth of 11 GHz. It has a maximum gain of 8.875 dB and demonstrates excellent isolation (-27.627 dB) and efficiency (98.859%), respectively. By designing and simulating a comparable RLC circuit in advanced design system (ADS), we have confirmed the accuracy and reliability of the data acquired via CST. Both CST and ADS simulators yielded similar reflection coefficients. This antenna is a superb option for the 38 GHz frequency range in 5G wireless communication.